The impact of nasogastric tube feeding on Drive for Thinness and Body Dissatisfaction in children and adolescents with Anorexia Nervosa - J. Pruccoli; M. Pelusi; G. Romagnoli; A. Parmeggiani (European Psychiatry, 2022)
Introduction The use of nasogastric-tube feeding (NGT) in the treatment of Anorexia Nervosa (AN) in children and adolescents is recommended by current guidelines. Nonetheless, the literature lacks studies assessing prognostic factors for modifications of AN-specific psychopathology treated with NGT.